Soluble CD163 Made by Monocyte/Macrophages Is a Novel Marker of HIV Activity in Early and Chronic Infection Prior to and After Anti-retroviral Therapy - Tricia H. Burdo; Margaret R. Lentz; Patrick Autissier; Anitha Krishnan; Elkan F. Halpern; Scott Letendre; Eric Rosenberg; Ronald J. Ellis; Kenneth C. Williams (2011)
CD163, a monocyte- and macrophage-specific scavenger receptor, is shed during activation as soluble CD163 (sCD163). We have previously demonstrated that monocyte expansion from bone marrow with simian immunodeficiency virus (SIV) infection correlated with plasma sCD163, the rate of AIDS progression, and the severity of macrophage-mediated pathogenesis. Here, we examined sCD163 in human immunodeficiency virus (HIV) infection. sCD163 was elevated in the plasma of individuals with chronic HIV infection (>1 year in duration), compared with HIV-seronegative individuals. With effective antiretroviral therapy (ART), sCD163 levels decreased in parallel with HIV RNA levels but did not return to HIV-seronegative levels, suggesting the presence of residual monocyte/macrophage activation even with plasma viral loads below the limit of detection. In individuals with early HIV infection (≤1 year in duration), effective ART resulted in decreased sCD163 levels that were comparable to levels in HIV-seronegative individuals. sCD163 levels in plasma were positively correlated with the percentage of CD14+CD16+ monocytes and activated CD8+HLA-DR+CD38+ T lymphocytes and were inversely correlated with CD163 expression on CD14+CD16+ monocytes. With ART interruption in subjects with early HIV infection, sCD163 and plasma virus levels spiked but rapidly returned to baseline with reinitiation of ART. This study points to the utility of monocyte- and macrophage-derived sCD163 as a marker of HIV activity that links viral replication with monocyte and macrophage activation. These observations underscore the significance of monocyte and macrophage immune responses with HIV pathogenesis.